Fc multimers effectively treat murine models of multiple sclerosis - Wang, Jin; Brown, Kellie; Danehy, Caroline; Mérigeon, Emmanuel; Goralski, Stephen; Rice, Samuel; Torgbe, Kwame; Thomas, Fridtjof; Block, David; Olsen, Henrik; Strome, Scott E.; Fitzpatrick, Elizabeth A. (Frontiers in Immunology, 2023)
Multiple Sclerosis (MS) is a chronic neurodegenerative disease with limited therapeutic options. Recombinant Fc multimers rFc), designed to mirror many of the anti-inflammatory activities of Intravenous Immunoglobulin (IVIG), have been shown to effectively treat numerous immunemediated diseases in rodents. In this study we used the experimental autoimmune encephalomyelitis (EAE) murine model of MS to test the efficacy of a rFc, M019, that consists of multimers of the Fc portion of IgG2, in inhibiting disease severity. We show that M019 effectively reduced clinical symptoms when given either pre-or post-symptom onset compared to vehicle treated EAE induced mice. M019 was effective in reducing symptoms in both SJL model of relapsing remitting MS as well as the B6 model of chronic disease. M019 binds to FcγR bearing-monocytes both in vivo and in vitro and prevented immune cell infiltration into the CNS of treated mice. The lack of T cell infiltration into the spinal cord was not due to a decrease in T cell priming; there was an equivalent frequency of Th17 cells in the spleens of M019 and vehicle treated EAE induced mice. Surprisingly, there was an increase in chemokines in the sera but not in the CNS of M019 treated mice compared to vehicle treated animals. We postulate that M019 interacts with a FcγR rich monocyte intermediary to prevent T cell migration into the CNS and demyelination.* Statistically significant on 5%-level with Holm-Bonferroni adjustment for multiplicity in pairwise comparisons (3 for each criterion). **Includes data up to and including day 21 post-immunization, the end of M019 treatment.